P151 Risk factors for first intestinal surgery in Crohn's disease. (25th January 2019) - Novacek, G; Reinisch, W; Reinisch, S; Primas, C; Eigner, W; Vogelsang, H; Dejaco, C; Kazemi-Shirazi, L; Niapir, M; Mekhail, P; Pedarnig, N; Angermann, H; et al.
Abstract: Background: Despite improved treatment options, intestinal complications and subsequent surgeries are still frequent in Crohn's disease (CD). We aimed to investigate the likelihood of first surgery in patients with CD treated at a tertiary centre and to explore potential risk factors early in the course of disease. Methods: This is a single-centre cohort study of 887 patients with CD (female 455; median age at diagnosis 25 years) usually referred after diagnosis. Medical characteristics were received from a validated database (IBDIS, Inflammatory Bowel Disease Information System). The primary end point was first intestinal surgery (resection, strictureplasty). Cox proportional hazard regression analysis was used to explore the impact of potential confounders on the time from diagnosis to first surgery or to last follow-up. The following variables were included in the analysis: diagnostic delay (time from symptom onset to diagnosis), immunosuppressive and/or biological treatment, location of disease, smoking habits, gender, and year of diagnosis. Hazard ratios (HR) with 95% confidence intervals (CI) are reported. Results: 457 (52%) patients underwent intestinal surgery during a median follow-up period of 13 years. After 12 years 50% of the patients had undergone first intestinal surgery. Forty-six per cent of patients received immunosuppressives and 35% of patients received biological treatment prior to first intestinal surgery. Ileal location, no immunosuppressive and no biological treatment and smoking were found to be significant as well as strong independent risk factors for first intestinal surgery in CD (Table). Patients with late initiation (after 2 years after diagnosis) of immunosuppressives as well as biologics tended to be at lower risk for surgery compared with patients with early initiation (within 2 years after diagnosis) (HR 0.736, 95% CI 0.503–1.078 and HR 0.588, 95% CI 0.330–1.046). Diagnostic delay, gender and year of diagnosis had no significant influence on the risk of surgery. Conclusions: Patients with ileal location, without treatment with immunosuppressives or biologics, as well as smokers are more likely to undergo first intestinal surgery in CD. Even late initiation of immunosuppressive as well as biological treatment might avert this risk of surgery in CD patients.